Ash Particles Detected in the Tropical Lower Stratosphere. Issue 20 (29th October 2018) - Jensen, Eric J.; Woods, Sarah; Lawson, R. Paul; Bui, T. Paul; Pfister, Leonhard; Thornberry, Troy Dean; Rollins, Andrew W.; Vernier, Jean‐Paul; Pan, Laura L.; Honomichl, Shawn; Toon, Owen Brian
Abstract: We report here on measurements of relatively large (up to ≃5‐μm maximum dimension) particles detected in the tropical western Pacific lower stratosphere. The particles were observed at low relative humidities and contain no detectable ice mass. We conclude that these particles are silicate ash injected by the Mount Kelud eruption in Indonesia a few weeks prior to the aircraft observations. The Kelud ash particles were detected by cloud probes on the National Aeronautics and Space Administration Global Hawk between the lapse rate tropopause (≃16.5 km) and the aircraft ceiling (18.5 km). The ash particles detected in the lowermost stratosphere by the aircraft extended well into the northern subtropics. The concentration of ash particles dropped off rapidly below the lapse rate tropopause, presumably because of rapid removal by ice nucleation scavenging. Although ash particles are very effective ice nuclei, the low particle concentrations detected in the upper troposphere precludes a significant impact on cirrus clouds. Plain Language Summary: We report here on measurements of relatively large (up to  5‐μm maximum dimension) particles detected in the tropical western Pacific lower stratosphere during the National Aeronautics and Space Administration Airborne Tropical TRopopause EXperiment Global Hawk flights in early March 2014. The particles were observed at low relative humidities and contain no detectable ice mass. We conclude that these particles are silicate ash injected by the Mount Kelud volcanic eruption in Indonesia a few weeks prior to the Airborne Tropical TRopopause EXperiment flights. The Kelud ash particles were detected by cloud probes on the Global Hawk between the lapse rate tropopause (16.5 km) and the aircraft ceiling (18.5 km). The ash particles sampled in the lowermost stratosphere by the aircraft extended further north than the Kelud plume measured by spaceborne lidar at higher altitudes. The concentration of ash particles dropped off rapidly below the lapse rate tropopause, presumably because of rapid removal by ice nucleation on the ash particles followed by ice crystal sedimentation. Although ash particles are very effective ice nuclei, the low particle concentrations detected in the upper troposphere preclude a significant impact on cirrus microphysical properties. Key Points: Large (5 microns) ash particles detected in the tropical lowermost stratosphere Ash particles were from the Mount Kelud eruption and persisted in the stratosphere for 4 weeks The low ash particle concentration indicates a limited impact on ice clouds or radiation